2021
DOI: 10.3390/healthcare9020116
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Policies Based on the Multi-Fuzzy Regression Discontinuity, in Terms of the Number of Deaths in the Coronavirus Epidemic

Abstract: It has been a year since the outbreak of the coronavirus epidemic 2019 (COVID-19). In the face of the global epidemic, governments in all countries have taken different prevention measures, such as social isolation, mandatory health protection, and the closure of schools and workplaces. The situation of the epidemic has clearly varied from country to country. In this context, research on the impact of policies for the control of the spread of the global epidemic is of great significance. In this paper, we exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Similarly, Wang et al (2019) showed that in northern China, air quality has gradually improved due to a series of heating policy changes implemented by the central government in recent years. Wang et al (2021) analysed the correlation between the policy stringency index and the number of deaths from COVID-19 in the world. They showed that policy control measures had a significant effect on epidemic control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Wang et al (2019) showed that in northern China, air quality has gradually improved due to a series of heating policy changes implemented by the central government in recent years. Wang et al (2021) analysed the correlation between the policy stringency index and the number of deaths from COVID-19 in the world. They showed that policy control measures had a significant effect on epidemic control.…”
Section: Discussionmentioning
confidence: 99%
“…It began to be used increasingly in socio-economic analysis from the late 1990s onwards. Since then, there have been many articles in the fields of education, the labour market, forensics, environmental protection, and health care, on the economic impact of regulatory change (Lee and Munk 2008;Lee and Lemieux 2010;Dong et al 2019;Lotsu et al 2019;Wang et al 2019Wang et al , 2021Ogunmodede et al 2020;Song et al 2020;Zhao et al 2021).…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…Internet public opinion is an important feedback mechanism for the government’s risk management, and it is a “mirror” for the government to understand the people’s expectations and summarize political gains and losses [ 22 ]. By analyzing online public opinion data, checking and filling gaps in the process of public opinion screening, and taking targeted improvement measures, it is conducive to promoting the scientific and democratization of government risk management, and promoting governance innovation and improvement [ 23 , 24 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…One strand of literature has emerged on measuring the effects of potential benefit duration on unemployment duration [15][16][17][18]. Another strand in which RDD has been applied is the impact of regulatory changes on socio-economic phenomenon [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Hypothesis and The Research Objectivementioning
confidence: 99%